MicroRNA-Mediated Responses to Chromium Stress Provide Insight Into Tolerance Characteristics of Miscanthus sinensis - Nie, Gang; Liao, Zongchao; Zhong, Minyi; Zhou, Jie; Cai, Jiabang; Liu, Aiyu; Wang, Xia; Zhang, Xinquan (Frontiers in Plant Science, 2021)
Chromium (Cr) is a heavy metal in nature, which poses a potential risk to toxic to both animals and plants when releasing into the environment. However, the regulation of miRNA-mediated response to heavy metal Cr has not been studied in Miscanthus sinensis. In this study, based on high-throughput microRNA sequencing, a total of 104 conserved miRNAs and 158 non-conserved miRNAs were identified. Among them, there were 45 differentially expressed miRNAs in the root and 13 differentially expressed miRNAs in leaves. The hierarchical clustering analysis showed that these miRNAs were preferentially expressed in a certain tissue. There were 833 differentially expressed target genes of 45 miRNA in roots and 280 differentially expressed target genes in leaves. After expression trends analysis, five significantly enriched modules were obtained in root and three significantly enriched trend blocks in leaves. Based on candidate genes annotation and GO and KEGG function analysis, the miR167a, novel_miR15 and novel_miR22 and their targets were potentially involved in Cr transportation and chelation. Besides, miR156a, miR164, miR396d and novel_miR155 were identified participating in plant physiological and biochemical metabolism and the detoxification of Cr. The results demonstrated the critical role of microRNAs mediated responses to Cr treatment in Miscanthus sinensis, which involves ion uptake, transport, accumulation, and tolerance characteristics.